Design and implementation of a real-time monitoring system for solar photovoltaic systems - Tonny, Sanzida Islam; Shopno, MD Adil Islam; Utsho, K. M. Nafiul Islam; Diganta, Nafiul Islam (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.